Learning Ray : flexible distributed Python for machine learning - Pumperla, Max; Oakes, Edward; Liaw, Richard (O'Reilly Media, Inc., 2023)
Get started with Ray, the open source distributed computing framework that simplifies the process of scaling compute-intensive Python workloads. With this practical book, Python programmers, data engineers, and data scientists will learn how to leverage Ray locally and spin up compute clusters. You'll be able to use Ray to structure and run machine learning programs at scale.